2012
DOI: 10.1016/j.envpol.2012.04.032
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of human body concentrations of DDT from indoor residual spraying for malaria control

Abstract: Blood and breast milk samples from inhabitants living in dwellings treated with DDT in indoor residual spraying show high DDT levels. This is of concern since mothers transfer lipid-soluble contaminants such as DDT via breastfeeding to their children. We focused on DDT use in South Africa and used a pharmacokinetic model to identify the dominant DDT uptake routes (food vs. inhalation), to estimate DDT levels in human lipid tissue over the full lifetime of an individual, and to determine the amount of DDT trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 40 publications
1
8
0
1
Order By: Relevance
“…Therefore, biological activity of organochlorine pesticides in the human body can be related to its molecular structure and physical-chemical properties. Our results are in concordance with that of Malarvannan et al (2013), Dirtu et al (2013), andHerrero-Mercado et al (2011), indicating a potential steady redistribution of these pesticides among body compartments and low metabolic rate (Kim et al 2011;Gyalpo et al 2012). Recently, De Roos et al (2012) showed that indicators of greater adiposity (such as weight, body mass index, fat mass percent, subcutaneous abdominal fat, intra-abdominal fat, waist circumference, and hip circumference) were related to lower plasma concentrations of most organochlorine pesticides.…”
Section: Resultssupporting
confidence: 94%
“…Therefore, biological activity of organochlorine pesticides in the human body can be related to its molecular structure and physical-chemical properties. Our results are in concordance with that of Malarvannan et al (2013), Dirtu et al (2013), andHerrero-Mercado et al (2011), indicating a potential steady redistribution of these pesticides among body compartments and low metabolic rate (Kim et al 2011;Gyalpo et al 2012). Recently, De Roos et al (2012) showed that indicators of greater adiposity (such as weight, body mass index, fat mass percent, subcutaneous abdominal fat, intra-abdominal fat, waist circumference, and hip circumference) were related to lower plasma concentrations of most organochlorine pesticides.…”
Section: Resultssupporting
confidence: 94%
“…Despite evidence of potential harmful human health effects of DDT exposure, there remains a gap in knowledge regarding determinants and strategies for reduction of exposure, particularly among nonoccupationally exposed individuals (i.e., residents of IRS-treated homes). Few studies have examined determinants of body burden among this population, and those that have suggest that inhalation and food consumption are relevant routes of exposure (Gyalpo et al 2012; Ritter et al 2011). Although the majority of South Africa is considered a low-risk malaria area, malaria continues to be endemic in the Limpopo Province and IRS remains a mainstay of vector control (Moonasar et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In Mexico, as biomarkers of exposure, pesticide residues, especially organochlorine (OCP) and among the most important in the past dichlorodiphenyldichloroethane or DDT, have been found in the human abdominal and breast adipose tissue, human semen, blood serum, umbilical blood, serum, and breast milk, among inhabitants living in protected tropical areas [81][82][83][84][85][86][87][88][89][90][91][92]. These pesticides were also important, as they protected human and life stock from malaria.…”
Section: Biomarkers Of Exposurementioning
confidence: 99%